Semiotic language in the Architecture of Modern Style Commercial typology of the city of Managua - Aguilar Arriola, Erasmo José (2022)
In this article, the most outstanding aspects of Architectural Semiotics focused on the recognition of the elements within the typology of Shopping Centers in the city of Managua are addressed in a timely manner. Starting from different theorists and studies, the importance of semiotics is established as a method of architecture for its correct understanding and therefore also for the subsequent design process, taking up the elements and criteria that have a meaning to be highlighted and generate pleasure and identity. The identification of these components was obtained from the analysis of theories and concepts (texture, color, shapes, signs and sensations, emotions that are generated from the user experience) closely linked to the subject and whose synthesis allowed the creation of a methodology and , in turn, a specific tool that is synthesized in a table of values for the semiotic analysis in situ (Evaluation Sheet of Semiotic Analysis in Shopping Centers). It is important to recognize the general values of architectural works and the style they bring to the city, whether on a neighborhood scale or more macro. Although at the time these buildings stood out from the style of the areas where they are located, they quickly managed to become a development impetus for other works that followed, even generating an identity with the users.